3D printed porous biomass–derived SiCnw/SiC composite for structure–function integrated electromagnetic absorption. Issue 3 (3rd July 2022) - Wang, Changshun; Wu, Siqi; Li, Zhaoqing; Chen, Shuang; Chen, Annan; Yan, Chunze; Shi, Yusheng; Zhang, Haibo; Fan, Pengyuan
ABSTRACT: Ceramic-based absorbing composite is irreplaceable in high-temperature conditions. This work has fabricated a novel biomass–derived porous SiCnw/SiC composite for structure–function integrated electromagnetic wave (EMW) absorption through selective laser sintering (SLS) 3D printing and carbothermal reduction. SLS processed the biomass-derived wood precursor with unique porous microstructures. The structure–function properties were controlled by changing the SiO carbothermal reduction temperatures, which facilitated the growth of SiC nanowires for effective EMW absorption. The 3D printed porous SiCnw/SiC composite shows efficient EMW absorption abilities with a minimum reflection loss of −49.01 dB and an effective absorption bandwidth of 5.1 GHz. The bulk density and flexural strength of porous SiCnw/SiC composite are respectively 0.73 ± 0.001 g/cm 3 and 6.21 ± 0.66 MPa. Despite a high open porosity of 75.58 ± 0.31%, the porous SiCnw/SiC composite demonstrates excellent thermal conductivities of 3.21∼4.99 W/(m·K) and superior fire-resistant ability. The 3D printed SiCnw/SiC composite integrates structure and functions, indicating wide applications in specific harsh environments.